Involvement of the Precuneus/Posterior Cingulate Cortex Is Significant for the Development of Alzheimer’s Disease: A PET (THK5351, PiB) and Resting fMRI Study - Yokoi, Takamasa; Watanabe, Hirohisa; Yamaguchi, Hiroshi; Bagarinao, Epifanio; Masuda, Michihito; Imai, Kazunori; Ogura, Aya; Ohdake, Reiko; Kawabata, Kazuya; Hara, Kazuhiro; Riku, Yuichi; Ishigaki, Shinsuke; et al. (Frontiers in Aging Neuroscience, 2018)
Abstract Background: Imaging studies in Alzheimer’s disease have yet to answer the underlying questions concerning the relationship among tau retention, neuroinflammation, network disruption, and cognitive decline. We compared the spatial retention patterns of 18F-THK5351 and resting state network disruption in patients with early Alzheimer’s disease and healthy controls. Methods: We enrolled 23 11C-Pittsburgh compound B (PiB)-positive patients with early Alzheimer’s disease and 24 11C-PiB-negative participants as healthy controls. All participants underwent resting state functional MRI and 18F-THK5351 PET scans. We used scaled subprofile modeling/principal component analysis (SSM/PCA) to reduce the complexity of multivariate data and to identify patterns that exhibited the largest statistical effects (variances) in THK5351 concentration in Alzheimer’s disease and healthy controls. Findings: SSM/PCA identified a significant spatial THK5351 pattern composed by mainly three clusters including precuneus/posterior cingulate cortex, right and left dorsolateral prefrontal cortex which accounted for 23.6% of the total subject voxel variance of the data and had 82.6% sensitivity and 79.1% specificity in discriminating Alzheimer’s disease from healthy controls. There was a significant relationship between the intensity of the 18F-THK5351 covariation pattern and cognitive scores in Alzheimer’s disease. The spatial patterns of 18F-THK5351 uptake showed significant similarity with intrinsic functional connectivity, especially in the precuneus/posterior cingulate cortex network. Seed-based connectivity analysis from the precuneus/posterior cingulate cortex showed significant decrease in connectivity over widespread brain regions in Alzheimer’s disease patients. An evaluation of an autopsied Alzheimer’s disease patient with Braak V showed that 18F-THK5351 retention corresponded to tau deposition, monoamine oxidase-B and astrogliosis in the precuneus/posterior cingulate cortex. Interpretation: We identified an Alzheimer’s disease-specific spatial pattern of 18F-THK5351 retention in the precuneus/posterior cingulate cortex, an important connectivity hub region in the brain. Disruption of the functional connections of this important network hub may play an important role in developing dementia in Alzheimer’s disease.